2021
DOI: 10.1016/j.celrep.2021.109012
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical cell-type-specific functions of caspase-11 in LPS shock and antibacterial host defense

Abstract: SUMMARY Caspase-11 sensing of intracellular lipopolysaccharide (LPS) plays critical roles during infections and sepsis. However, the key cell types that sense intracellular LPS and their contributions to the host responses at the organismal level are not completely clear. Here, we show that macrophage/monocyte-specific caspase-11 plays a dominant role in mediating the pathological manifestations of endotoxemia, including gasdermin D (GSDMD) activation, interleukin (IL)-1β, IL-18, and damage-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Activated NLRP3 forms a protein complex (NLRP3 inflammasome) consisting of NLRP3, ASC and precaspase-1, and activated caspase-1 causes macrophage pyroptosis ( 97 ). To explore how macrophages perceive intracellular LPS and function in the host at the whole body level, Kumari et al ( 98 ) constructed a conditional knockout of caspase-11 from monocytes/macrophages, neutrophils, and dendritic cells in mice, and found that macrophage/monocyte-specific caspase-11 plays a leading role in mediating the pathological manifestations of endotoxemia, including the activation of GSDMD, IL-1β and IL-18, the release of DAMPs and tissue damage, proving that caspase-11 dependent macrophage pyroptosis is pivotal in the development of sepsis.…”
Section: Types Of Programmed Cell Death In Sepsis-akimentioning
confidence: 99%
“…Activated NLRP3 forms a protein complex (NLRP3 inflammasome) consisting of NLRP3, ASC and precaspase-1, and activated caspase-1 causes macrophage pyroptosis ( 97 ). To explore how macrophages perceive intracellular LPS and function in the host at the whole body level, Kumari et al ( 98 ) constructed a conditional knockout of caspase-11 from monocytes/macrophages, neutrophils, and dendritic cells in mice, and found that macrophage/monocyte-specific caspase-11 plays a leading role in mediating the pathological manifestations of endotoxemia, including the activation of GSDMD, IL-1β and IL-18, the release of DAMPs and tissue damage, proving that caspase-11 dependent macrophage pyroptosis is pivotal in the development of sepsis.…”
Section: Types Of Programmed Cell Death In Sepsis-akimentioning
confidence: 99%
“…Consistent with this observation, a recent study revealed that selective loss of Casp11 in Mpr8 + cells, comprising neutrophils and a small percentage of monocytes, did not protect mice from LPS‐induced caspase‐11 lethality, although caspase‐11 activity in Mpr8 + cells does appear to promote to tissue damage (Kumari et al, 2021). Instead, loss of Casp11 in endothelial cells (Cheng et al, 2017) or LysM + cells, which comprise macrophages, monocytes, and around 60% of neutrophils (Abram et al, 2014) conferred significant protection against caspase‐11‐dependent lethality (Kumari et al, 2021). Thus, inflammasome activity in neutrophils alone is unlikely to mediate immunopathology during LPS‐induced septic shock, unlike under conditions of Nlrp3 or Nlrc4 gain‐of‐function mutations (Nichols et al, 2017; Stackowicz et al, 2021).…”
Section: Neutrophil Elastase Cleaves Gsdmdmentioning
confidence: 59%
“…Although multiple studies have verified that neutrophils resist pyroptosis in caspase‐1 activated cells (Chen et al, 2014; Karmakar et al, 2020; Karmakar et al, 2016; Kovacs et al, 2020; Kumari et al, 2021), emerging literature revealed that GSDMD can in fact trigger neutrophil rupture under specific conditions, indicating that these cells are not intrinsically resistant to GSDMD pores. For instance, detection of cytoplasmic LPS or Gram‐negative bacteria promotes assembly of the noncanonical inflammasome, which triggers caspase‐11 activation, robust GSDMD cleavage and neutrophil lysis (Chen et al, 2018b; Figure 3).…”
Section: Active Caspase‐11 Triggers Gsdmd‐dependent Pyroptosis and Ne...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we next infected WT or Nlrc4 -/- BMNs with various bacteria ( Salmonella Typhimurium, Shigella flexnerii, Chromobacter violaceum, Burkholderia thailandensis ) known to trigger a NLRC4 inflammasome response and monitored for cell death and IL-1β release ( Fig. 3E ) [5,28,4446]. None of the tested bacteria triggered a significant NLRC4-dependent neutrophil lysis of murine neutrophils although they promoted NLRC4-dependent IL-1β release and Gasdermin D processing ( S2C Fig.…”
Section: Resultsmentioning
confidence: 99%